Development of a smart articulate storyline using teaching at the right level based learning tools to improve teaching skills - Aldina Eka Andriani; SrI Sulistyorini; Dewi Nilam Tyas (Universitas Papua, 2025)
Developing high-quality lesson plan requires a meticulous and systematic process, considering several key aspects. This study aims to describe the development design, assess the feasibility, and evaluate the effectiveness of smart class articulate storyline through the development of lesson plan based on teaching at the right level (TaRL) to improve the teaching skills of pre-service teacher professional education (PPG Prajabatan) students in the elementary school teacher education study program within the context of differentiated learning. This research used a research and development (R&D) approach, using the ADDIE model. The strength of this research lies in developing materials focusing on basic teaching skills through the TaRL approach, complemented by instructional practice videos and lesson plan that could be accessed anytime. The study results indicate that the smart class articulate storyline is categorized as highly feasible, with evaluations from media and content experts each scoring 95% in the